Pengaruh Budaya Kerja, Lingkungan Kerja, dan Disiplin Kerja terhadap Kinerja Karyawan - Detson Ray Halomoan Sitorus; Dimas Agustian; Hendrikus Hironimus Botha; Handrianus Vianey Melin Wula (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
Public services provided by local governments are essential administrative functions, with the government serving as the sole provider. Consequently, the public’s reliance on these services underscores the importance of maintaining high levels of employee performance. Employee performance is influenced by various organizational and individual factors, particularly work culture, work environment, and work discipline. This study investigates the extent to which these three factors affect employee performance. A quantitative research design was employed, targeting a population of 43 employees. The study used a probability sampling technique, specifically simple random sampling, to select a sample of 38 respondents. Data were analyzed using both descriptive and inferential statistical methods. Descriptive statistics, including frequency analysis, were used to determine the mean scores for each item. Inferential analysis applied multiple linear regression to examine the effects of the independent variables on the dependent variable. The results indicated a positive association between work culture and employee performance; however, the effect of work culture was not statistically significant, with a t-value of 0.246 exceeding the 0.05 significance threshold. In contrast, both the work environment and work discipline had statistically significant and positive effects on employee performance when examined independently. Furthermore, a combined analysis of work culture, work environment, and work discipline revealed a significant joint influence on employee performance, as reflected by an F-value of 30.078 and a p-value below 0.05. In conclusion, while work culture alone may not significantly enhance performance, the collective influence of work culture, work environment, and work discipline is critical in improving employee outcomes. These findings suggest that organizations should prioritize these factors to optimize employee performance and achieve broader organizational objectives.